Effect of green tea extract on bonding durability of an etch-and-rinse adhesive system to caries-affected dentin - Carolina CARVALHO; Fernando Pelegrim FERNANDES; Valeria da Penha FREITAS; Fabiana Mantovani Gomes FRANÇA; Roberta Tarkany BASTING; Cecilia Pedroso TURSSI; Flávia Lucisano Botelho AMARAL
ABSTRACT Objective Green tea extract has been advocated as a matrix metalloproteinase (MMP) inhibitor; however, its effect on bond durability to caries-affected dentin has never been reported. Thus, the aim of this in vitro study was to evaluate the effect of two MMP inhibitors (2% chlorhexidine and 2% green tea extract), applied after acid etching, on bond durability of an etch-and-rinse adhesive system to caries-affected dentin. Material and Methods Occlusal enamel was removed from third molars to expose the dentin surface, and the molars were submitted to a caries induction protocol for 15 days. After removal of infected dentin, specimens were conditioned with 37% phosphoric acid (15 seconds) and randomly divided into three groups, according to the type of dentin pretreatment (n=10): NT: no treatment; GT: 2% green tea extract; CLX: 2% chlorhexidine. The etch-and-rinse adhesive system (Adper™ Single Bond 2, 3M ESPE, St. Paul, MN, USA) was applied according to the manufacturer's instructions, and composite resin restorations were built on the dentin. After 24 hours, at 37°C, the resin-tooth blocks were sectioned perpendicularly to the adhesive interface in the form of sticks (0.8 mm2 of adhesive area) and randomly subdivided into two groups according to when they were to be submitted to microtensile bond strength (μTBS) testing: immediately or 6 months after storage in distilled water. Data were reported in MPa and submitted to two-way ANOVA for completely randomized blocks, followed by Tukey's test (α=0.05). Results After 24 hours, there was no significant difference in the μTBS of the groups. After 6 months, the GT group had significantly higher μTBS values. Conclusion It was concluded that the application of 2% green tea extract was able to increase bond durability of the etch-and-rinse system to dentin. Neither the application of chlorhexidine nor non-treatment (NT - control) had any effect on bond strength after water storage.